SnRK1 activation, signaling, and networking for energy homeostasis. (October 2019) - Crepin, Nathalie; Rolland, Filip
Highlights: While SnRK1/SNF1/AMPK structure and function are well conserved, plants have modified SnRK1 regulation to better fit their unique lifestyle. Rather than being activated by low energy stress, SnRK1 appears to be repressed by high energy signals, such as trehalose-6-P (T6P). The group C/S1 bZIP TFs play a key role in the transcriptional reprogramming by SnRK1, regulating both growth and metabolism. SnRK1 functions in an intricate network with the growth-stimulating and antagonistic TOR pathway and ABA-activated SnRK2 signaling. Bypassing trade-offs between crop growth and stress tolerance will require more profound insight in the SnRK1-TOR-SnRK2 network. Abstract : The SnRK1 kinases are key regulators of the plant energy balance, but how their activity is regulated by metabolic status is still unclear. While the heterotrimeric kinase complex is well conserved among plants, fungi, and animals, plants appear to have modified its regulation to better fit their unique physiology and lifestyle. The SnRK1 kinases control metabolism, growth, and development, and stress tolerance by direct phosphorylation of metabolic enzymes and regulatory proteins and by extensive transcriptional regulation. Diverse types of transcription factors have already been implicated, with a well-studied role for the heterodimerizing group C and group S1 bZIPs. SnRK1 is also part of a more elaborate metabolic and stress signaling network, which includes the TOR kinase and the ABA-signaling SnRK2 kinases.